Ahammu Al-Mukholafat Wa Al-Masail Al-Fiqhiyyah Fii Al-Haj Allati Tasahala Fiha Hujjaj Indonesia Fii Dhou'i Al-Madzahib Al-Arba'ah - Abdurrahman, Mifdhol; , Dr. Khoirudin Hamsin; , Dr. M. Abdul Kholiq Hasan, M.A (2016)
Fiqih Laws usually Underestimated Indonesian Pilgrims Reviewed by Four Schools Doing the pilgrimage to the holy land is the obligation of all Muslims who are able once in their lifetime. Unfortunately, while doing this, many Indonesion pilgrims today violate Islamic Fiqih laws related to the pilgrimage derectly sourced from Al Qur'an and Sunna of the Prophet, along with the stipulations of scholars from four muktabarah schools. This motivated the author to study further laws which are most commonly underestimated, ignored, and violated by Indonesian pilgrims. It drew the author's interest as a someone who works in pilgrimage and umrah service to formulate actions which can be taken to solve this problem. Therefore, the problem discussed in this thesis was the consistence between the practice of pilgrimage of Indonesian pilgrims and fiqih laws? And if there is any violation or mistake or law which is ignored or underestimated, this thesis tried to identify factors which cause it to happen and the solutions which can be offered to anticipate and solve it so that the pilgrimage of the pilgrims is perfect. Further, this thesis describes the opinions of scholars from four schools on laws which are usually underestimated. Therefore, the author/ researcher tries to articulate various fiqih laws related to pilgrimage and the underestimation of laws by Indonesian pilgrims by descriptive analytical method. Of course, the author complete this study by reconstructive- articulating analysis using the principles of relevant UsulFiqih science to synchronize the implementation of law on one hand and methodological principles on the other. After definig pilgrimage, legality, importance, requirements of implementation, principles, obligarions, and the sunna, as well as four fiqihh schools, the discussion in this study is classified into several major problems in Islamic fiqih related to violations of pilgrimage fiqih, such as: problems related to ihram, thowaf, sa'I, tarwiyah, wukuf in Arofah, mabit in Muzdalifah, mabitini Mina on tasyriq day, and towafwada'. This scientific study is closed by not only mentioning various Islamic fiqih laws usually underestimated by Indonesian pilgrims, but also formulation of their causes, whether internal (from inside the pilgrims0 or external which involves Islamic and government institutions. This scientific study also tries to formulate strategic steps recommended for the pilgrims and for the stakeholders of pilgrimage service, such as the Ministry of Religion and pilgrimage service companies. Keyword: Pilgrim, Hajj, Islamic Fiqih Law, Underestimate, Four Schools